2023
DOI: 10.3390/w15040741
|View full text |Cite
|
Sign up to set email alerts
|

A Review of HYDRUS 2D/3D Applications for Simulations of Water Dynamics, Root Uptake and Solute Transport in Tree Crops under Drip Irrigation

Abstract: Orchards with tree crops are of critical importance to the global economy and to the environment due to their ability to be productive for many years without the need for replanting. They are also better adapted to extreme climatic conditions compared to other crops. However, new challenges are emerging as climate change threatens both tree production and water supply. Drip irrigation (surface and subsurface) is an irrigation method that has the potential to save water and nutrients by placing water directly i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 81 publications
0
1
0
Order By: Relevance
“…Another more narrowly focused review was written by Morianou et al. (2023). They looked at HYDRUS applications for simulations of water dynamics, RWU, and solute transport under drip irrigation of the four most common categories of tree crops (citrus, olive, avocado, and deciduous fruit/nuts).…”
Section: Discussion Of Recent Developments and Applicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another more narrowly focused review was written by Morianou et al. (2023). They looked at HYDRUS applications for simulations of water dynamics, RWU, and solute transport under drip irrigation of the four most common categories of tree crops (citrus, olive, avocado, and deciduous fruit/nuts).…”
Section: Discussion Of Recent Developments and Applicationsmentioning
confidence: 99%
“…They looked at HYDRUS applications for simulations of water dynamics, RWU, and solute transport under drip irrigation of the four most common categories of tree crops (citrus, olive, avocado, and deciduous fruit/nuts). Morianou et al (2023) identified 22 papers dealing with this topic, most of which involved surface drip irrigation, while three also focused on subsurface drip irrigation.…”
Section: Irrigation Applicationsmentioning
confidence: 99%
“…In order to achieve the most cost-effective and efficient solution, researchers have utilized advanced numerical models like HYDRUS 1D/2D/3D to determine the ideal combination of irrigation management and design [10]. HYDRUS is a reliable and widely used software program designed for simulating the movement of solutes, heat, and water in variably saturated porous surfaces in all dimensions.…”
Section: Of 16mentioning
confidence: 99%
“…These findings correspond to the study [42] based on their research, in which drip irrigation systems, rainwater harvesting, and responsive drip irrigation can help farmers efficiently use water in rainfed regions such as the Soan River Basin. Adapting efficient drip irrigation systems for agriculture can provide sustainability for agriculture and water resources [43][44][45]. Likewise, using green and water infrastructure in society can mitigate the global warming issue.…”
Section: Climate Change Adaptation and Mitigation Strategiesmentioning
confidence: 99%